Itraconazole-induced Torsade de Pointes in a patient receiving methadone substitution therapy - Robson, N.Z.; Vicknasingam, B.; Narayanan, S. (Wiley-blackwell publishing, inc Malden, 2009)
Issues. Methadone, a pharmacological agent used to treat heroin dependence is relatively safe, but may cause cardiac arrhythmias in the concurrent presence of other risk factors. Approach and Key Findings. This case report highlights the risk of Torsade de Pointes, a life-threatening cardiac arrhythmia, in a heroin-dependent patient receiving methadone substitution therapy who was prescribed itraconazole for vaginal thrush. The patient presented to the accident and emergency department for chest discomfort and an episode of syncope following two doses of itraconazole (200 mg). Electrocardiogram monitoring at the accident and emergency department showed prolonged rate-corrected QT interval leading to Torsade de Pointes. The patient was admitted for cardiac monitoring, and electrocardiogram returned to normal upon discontinuation of methadone. Implication. This cardiac arrhythmia was most likely as a result of a drug interaction between methadone and itraconazole because the patient presented with no other risk factors. Conclusion. Given the benefits of methadone as a substitution treatment for heroin-dependent individuals, the association between methadone and cardiac arrhythmias is of great concern. Physicians treating heroin-dependent patients on methadone substitution therapy should therefore be cautious of the potential risk of drug interactions that may lead to fatal cardiac arrhythmias. [NoorZurani MHR, Vicknasingam B, Narayanan S. Itraconazole-induced Torsade de Pointes in a patient receiving methadone substitution therapy. Drug Alcohol Rev 2009;28:688-690].